Surgical Challenges Associated With Anterior Choroidal Artery Aneurysm Clipping: 2‐Dimensional Operative Video. Issue 3 (September 2020) - Hendricks, Benjamin K.; Spetzler, Robert F.
Abstract : N/A: Surgical treatment of anterior choroidal artery (AChA) aneurysms is challenging because of the constrained operative corridor and limitations imparted by the surrounding rigid structures during the exposure. The AChA most commonly arises as a single branch from the communicating (C7) segment of the internal carotid artery but has 2 to 4 branches in approximately one‐third of cases, and aneurysms generally arise from the parent vessel interface with these branches. This patient experienced a sentinel headache 4 d before presenting with subarachnoid hemorrhage. The patient had a large right AChA aneurysm with a unique configuration in which the parent vessel was located anterior to the aneurysm. Endovascular therapy was aborted because there was an AChA branch at the base of the aneurysm. An orbitozygomatic craniotomy was performed that provided transsylvian access to the region of interest. Clip application was challenging because of the close proximity of the branch vessels. Intraoperative indocyanine green evaluation and postoperative angiogram showed patency of the AChA and posterior communicating artery. This video demonstrates the surgical challenge associated with AChA aneurysms because of the proximity of adjacent structures and highlights the importance of meticulous technique during clip application. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .